2018
DOI: 10.1159/000492230
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Electrode Contacts for Clinically Effective Deep Brain Stimulation in Essential Tremor

Abstract: Background/Aim: Deep brain stimulation (DBS) is an established neurosurgical treatment that can be used to alleviate symptoms in essential tremor (ET) and other movement disorders. The aim was to develop a method and software tool for the prediction of effective DBS electrode contacts based on probabilistic stimulation maps (PSMs) in patients with ET treated with caudal zona incerta (cZi) DBS. Methods: A total of 33 patients (37 leads) treated with DBS were evaluated with the Essential Tremor Rating Scale (ETR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 34 publications
(29 reference statements)
0
19
0
Order By: Relevance
“…Several attempts to predict postoperative tremor suppression focused on connectivity analysis or probabilistic stimulation mapping [1517]. However, only Åström et al [18] focused on predicting the DBS contact to be chosen postoperatively. Based on probabilistic stimulation maps, the resulting software tool, showed that the predicted contact with rank 1 matched the clinically used contact in 60% of cases (rank 1-2 matched 83% of the cases).…”
Section: Discussionmentioning
confidence: 99%
“…Several attempts to predict postoperative tremor suppression focused on connectivity analysis or probabilistic stimulation mapping [1517]. However, only Åström et al [18] focused on predicting the DBS contact to be chosen postoperatively. Based on probabilistic stimulation maps, the resulting software tool, showed that the predicted contact with rank 1 matched the clinically used contact in 60% of cases (rank 1-2 matched 83% of the cases).…”
Section: Discussionmentioning
confidence: 99%
“…This can lead to a lack of details of the small deep brain structures which are of high importance for DBS procedures ( Ou et al, 2014 ). For that reason, several studies have been based on group-specific templates from patients undergoing DBS ( Åström et al, 2018 ; Johnson et al, 2019 ).…”
Section: Deep Brain Anatomical Templates and Group Analysismentioning
confidence: 99%
“…To estimate the electrical effect of stimulation in a patient, several authors include the location and symptomatic effect of the contact of the electrode used for long-term stimulation ( Fytagoridis et al, 2013 ; Lalys et al, 2013 ). In contrast, a more precise estimation can be done by using in silico simulations of single patient distribution of the EF ( Åström et al, 2010 , 2018 ; Hemm et al, 2016 ; Akbarian-Tefaghi et al, 2017 ; Naesstrom et al, 2021 ). Implementation of this method can also be expanded to visualize induced improvements and adverse effects in patient-specific stimulation maps ( Shah et al, 2020 ).…”
Section: Deep Brain Anatomical Templates and Group Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The goal of this session is to find optimal settings that stimulate the target region, while avoiding regions that cause side-effects. A detailed understanding of the spatial relationship between target structure, region of avoidance, and the implanted electrode, can provide valuable information for the time-consuming process of fine-tuning stimulation parameters [17,18,19].…”
Section: Introductionmentioning
confidence: 99%